Public Libraries in Jaffna District, Sri Lanka – Challenges - Chandrasekar, K. (Libraries at University of Nebraska-Lincoln, Library Philosophy and Practice (e-journal), 2013)
Establishment of public libraries is regarded as one of the essential amenities of the local or central government of a nation since they enhance the idea of free and equal access to information and offers their collections and services to all members of the community. This study revealed the present status of the public libraries in the Jaffna District. Apart from the Jaffna Public Library, which is managed by the Jaffna Municipal Council and provide services to the whole Jaffna District, presently there are 03 Urban Council libraries, 13 Pradeshiya Sabha libraries and 907 Community Center libraries, which cater the needs of the general public of the respective areas in the Jaffna District. Conflict situation which prevailed in the region for the past 30 years severely affected the library services, too. After signing the MOU between the Government of Sri Lanka and LTTE in 2002, many foreign and local Non-governmental organisations and United Nations agencies started to reconstruct and develop some of the public libraries of Jaffna District with the foreign funded projects. This study identified the major challenges for these public libraries, at present. Those are insufficient funding and inadequate infrastructure facilities, poor collection of e-resources and use of IT, dearth of professional and personal competencies among library staff, poor participation in CPD programs, lack of interest and motivation from authorities, and absence of library cooperation. It is recommended to have advocacy programs for all the stakeholders of these public libraries, adopt modern etechnology services in the library functionalities, organise regular user education programs for readers with regard to library services, conduct CPD programs and training sessions especially for the enhancement of professional and personal competencies among librarians of this region, and establish a library consortia to coordinate the activities of the libraries in the Jaffna District. With this type of support, public libraries of this region are expected to survive, and also thrive in continuing to provide valuable service in the information age.
Keywords: Public libraries; Challenges to libraries; Public libraries – Sri Lanka